Alternative diagnoses based on CT angiography of the chest in patients with suspected pulmonary thromboembolism - Ferreira,Eleci Vaz (2016)
Objective : To determine the prevalence of alternative diagnoses based on chest CT angiography (CTA) in patients with suspected pulmonary thromboembolism (PTE) who tested negative for PTE, as well as whether those alternative diagnoses had been considered prior to the CTA. Methods : This was a cross-sectional, retrospective study involving 191 adult patients undergoing CTA for suspected PTE between September of 2009 and May of 2012. Chest X-rays and CTAs were reviewed to determine whether the findings suggested an alternative diagnosis in the cases not diagnosed as PTE. Data on symptoms, risk factors, comorbidities, length of hospital stay, and mortality were collected. Results : On the basis of the CTA findings, PTE was diagnosed in 47 cases (24.6%). Among the 144 patients not diagnosed with PTE via CTA, the findings were abnormal in 120 (83.3%). Such findings were consistent with an alternative diagnosis that explained the symptoms in 75 patients (39.3%). Among those 75 cases, there were only 39 (20.4%) in which the same alterations had not been previously detected on chest X-rays. The most common alternative diagnosis, made solely on the basis of the CTA findings, was pneumonia (identified in 20 cases). Symptoms, risk factors, comorbidities, and the in-hospital mortality rate did not differ significantly between the patients with and without PTE. However, the median hospital stay was significantly longer in the patients with PTE than in those without (18.0 and 9.5 days, respectively; p = 0.001). Conclusions : Our results indicate that chest CTA is useful in cases of suspected PTE, because it can confirm the diagnosis and reveal findings consistent with an alternative diagnosis in a significant number of patients.